2008
DOI: 10.1021/jp806436n
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of Jet-Cooled Bi3

Abstract: A resonant two-photon ionization spectroscopic study of jet-cooled Bi3 has identified two band systems in the molecule in the 9600-10 600 and 15 250-16 050 cm(-1) range. The latter of these has been previously observed in matrix isolation spectroscopy and tentatively attributed to Bi4; the mass-resolved work presented here reassigns it to Bi3. A review of all previously observed electronic states is presented, and it is argued that the new band system lying in the range 9600-10 600 cm(-1) corresponds to the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 65 publications
(178 reference statements)
3
9
0
Order By: Relevance
“…In the following sections, we revise our previous argument by showing evidence for the presence of another low-lying electronic state locating above the ground state by ∼1870 cm –1 . The new assignment provides better consistency with the preceding experiments by photoelectron spectroscopy and resonant two-photon ionization spectroscopy, both combined with mass-selective detection of bismuth trimer in the gas phase.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…In the following sections, we revise our previous argument by showing evidence for the presence of another low-lying electronic state locating above the ground state by ∼1870 cm –1 . The new assignment provides better consistency with the preceding experiments by photoelectron spectroscopy and resonant two-photon ionization spectroscopy, both combined with mass-selective detection of bismuth trimer in the gas phase.…”
Section: Resultssupporting
confidence: 67%
“…31 The series of bands following the origin band at 9626.3 cm −1 with a peculiar vibrational progression of 130.0 cm −1 in the upper electronic state corresponds to the absorption spectrum for the electronic transitions in β system. The band origin at 9625 cm −1 in solid Ne is in good agreement with that at 9626.3 cm −1 in the gas phase, consistent with the assignment of the carrier to the trimer, Bi 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 Bi + n cations 18 have been identified mass spectroscopically to n > 40, and photofragmentation of small Bi cluster cations has been observed. 19,20 In addition to measurements on Bi 2 and Bi 4 (in solid Ne and Ar matrices), 21 on anions Bi − 2 , Bi − 3 , and Bi − 4 , 22 and on jet-cooled Bi 3 , 23 it has been found that neutral Bi n clusters up to n = 20 show paramagnetic deflections in Stern-Gerlach experiments for odd n. 24 Simulations of liquid pnictogens include work on As, Sb, and Bi by Hafner and Jank, 25 who performed molecular dynamics on samples with up to 2000 atoms using an effective pair potential. They showed that the open structures could be interpreted as a modulation of random packing by oscillations in the effective potentials.…”
Section: Introductionmentioning
confidence: 99%